Sustainable development scenarios: assessment of risks related to Ukraine’s economic security - Polovenko, Vitaliy; Ostapenko, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
Background. Despite significant progress in the study of Ukraine’s macroeconomic, industrial, financial, foreign economic, investment and innovation, social, and food security, a number of aspects of the overall problem remain insufficiently addressed or require additional attention in the context of current challenges caused by war and economic instability. Unresolved parts of the overall problem include labor shortages, insufficient support for the manufacturing industry, high import dependence, underfunding of science, overburdened social infrastructure, environmental threats, logistical constraints, and low trust in fiscal authorities. Addressing these challenges requires the development of targeted government programs, enhanced international cooperation, and private sector involvement to ensure Ukraine’s sustainable recovery. Methods. The study applies generalization and comparative analysis of the results of expert-analytical approaches, including forecasting, using institutional statistical sources. Results. The article highlights the results of a comprehensive analysis of the state of Ukraine’s economic, industrial, financial, foreign economic, investment and innovation, social, and food security in 2024, conducted considering current economic challenges impact. This analytical basis may further enable the development of a corresponding forward-looking projection for the period 2025–2027. Conclusions. The article uses the results of expert-analytical approaches, including statistical data analysis, risk assessment, and forecasting of trends in the macroeconomic, industrial, financial, and other key dimensions of Ukraine’s security architecture. A comparative analysis of major indicators was conducted, focusing on the transformation of challenges under wartime conditions. Special attention is devoted to the institutional and functional analysis of reforms based on recommendations of state and international organizations. These methods made it possible to outline strategic policy directions and develop scenarios for sustainable development in 2026–2027.